P109 CORONARY FLOW VELOCITY RESERVE REDUCTION IS ASSOCIATED WITH CARDIOVASCULAR, CANCER, AND NONCANCER, NONCARDIOVASCULAR MORTALITY. (18th May 2022) - Tuttolomondo, D; Suma, S; Botti, A; Gaibazzi, N
Abstract: Background: Coronary flow velocity reserve (CFVR) measured in the left anterior descending artery during high–dose vasodilator stress echocardiography interrogates both epicardial and microcirculatory coronary function and has been inversely associated with chronic inflammation and microvascular dysfunction, as well as with the presence of obstructive coronary artery disease. Microvascular dysfunction and chronic inflammation are common mechanisms of disease in cardiovascular (CV) and non–CV conditions. We aimed to assess whether CFVR is associated with all–cause death, but more specifically with CV, cancer, and non–CV and noncancer (NCVNC) mortality, independently and increasingly over other demographic, clinical, and echocardiography variables. Methods: One thousand two patients who underwent stress echocardiography were followed for a median of 8.2 years, with clinical, regional wall motion abnormalities (RWMAs), and CFVR data. The independent prognostic value of RWMA and CFVR regarding CV, cancer, or NCVNC mortality was evaluated adjusting for clinical variables. A prespecified subgroup of subjects with no RWMA or revascularization procedures during follow–up was also analyzed (n = 752), to exclude most participants with possible coronary artery disease and remove such confounding from the assessment of the potential association of CFVR and mortality. Results: A total of 161 patients (16%) died, 63 deaths being CV (39%), 52 from cancer (32%), and 46 (29%) from NCVNC causes. In comparison to CV mortality, cancer and NCVNC mortality were not associated with an ischemic RWMA at univariable analysis, while a CFVR < 2 was significantly associated with each category of cause–specific mortality. A CFVR < 2 or ≥ 2 separated a group of patients with 8–year 14.6% versus 1.2% CV mortality, 10.3% versus 0.4% cancer mortality, and 9.5% versus 1.5% NCVNC mortality. Conclusions: The reduction of CFVR is independently associated with CV, cancer, and NCVNC death in a population clinically referred for suspected/known coronary artery disease. CFVR can act as a marker or a mechanism preceding and predicting mortality from a wide variety of diseases.